Hubungan Kualitas Pelayanan Bagian Pendaftaran Rawat Jalan terhadap Kepuasan Pasien - Triana, Neni; Darmansyah, M Ari (JURNAL KESEHATAN TERAPAN, 2025)
Service quality has a direct impact on patient satisfaction assessments. In Purwodadi Regency there are only twelve hospitals. One ofthese Health Care is Puskesmas X, which is the most preferred reference by the public. The aim of this research is to determine therelationship between service quality in the registration department and outpatient satisfaction at X Palembang Health Care. The approach taken in this research is quantitative-analytic with a cross sectional study. This research was carried out from Oktober to November 2023. Samples were taken using accidental sampling with a population of 107,520 patients and samples taken of 100respondents using the Slovin formula calculation. The research instrument used a structured questionnaire. The results of theresearch show that there is a relationship between the quality of registration department services and outpatient satisfaction atPuskesmas X Palembang which includes components: tangibles with a p-value of 0.000 < 0.05; reliability with p-value 0.006 <0.05; responsiveness with p-value 0.000 < 0.05; assurance with a p- value of 0.000 < 0.05; and empathy with a p-value of 0.000 < 0.05. Overall, the total percentage of patient satisfaction is 70%. Thus, it can be concluded that to increase patient satisfactionscores, Health Care are obliged to improve the quality of service in every department.